2021
DOI: 10.1055/a-1471-5311
|View full text |Cite
|
Sign up to set email alerts
|

Empfehlungen des Antibiotic-Stewardship Teams – eine Analyse unter Routinebedingungen eines Universitätsklinikums

Abstract: Zusammenfassung Ziel der Studie Ziel dieser Studie war es, die Empfehlungen eines etablierten ABS-Teams während der wöchentlichen Routinevisiten zu evaluieren sowie ihre Umsetzungsrate und die Gründe der Nichtumsetzung zu untersuchen. Methodik Die Visiten eines multiprofessionellen ABS-Teams (Infektiologie, Mikrobiologie, Apotheke und Krankenhaushygiene) wurden über 8 Wochen auf 9 intensivmedizinischen und peripheren Stationen eines Universitätsklinikums (1451 Betten) begleitet. Die Empfehlungen des ABS-Teams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The increased documentation of medication errors associated with anti-infective drugs may be due to the fact that the efforts of clinical pharmacists to participate in antibiotic stewardship teams have increased steadily in recent years. 17,23 Moreover, Langebrake et al identified the inappropriate use of drugs followed by incorrect Table 3. Examples for the main categories of errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased documentation of medication errors associated with anti-infective drugs may be due to the fact that the efforts of clinical pharmacists to participate in antibiotic stewardship teams have increased steadily in recent years. 17,23 Moreover, Langebrake et al identified the inappropriate use of drugs followed by incorrect Table 3. Examples for the main categories of errors.…”
Section: Discussionmentioning
confidence: 99%
“…The increased documentation of medication errors associated with anti-infective drugs may be due to the fact that the efforts of clinical pharmacists to participate in antibiotic stewardship teams have increased steadily in recent years. 17,23 Moreover, Langebrake et al identified the inappropriate use of drugs followed by incorrect dosing as the most common reason for pharmaceutical intervention. In our data-set from the field of oncology, an incorrect dosing played an important role as well, followed by drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The Leipzig University Hospital (LUH) is a 1,451-bed tertiary-care facility with 29 departments and clinics of all specialties in Leipzig, Germany. Since 2012, several interdisciplinary AMS interventions have been implemented, including regular ward visits by the AMS team, intense training of staff, restriction of selected reserve antibiotics, surveillance of antibiotic consumption and resistance and the implementation of professional ISGs, as described before [ 17 , 22 24 ].…”
Section: Methodsmentioning
confidence: 99%